TOWARDS ACHIEVING SUSTAINABLE DEVELOPMENT GOAL IN QUALITY LEGAL EDUCATION: AN ANALYSIS OF CLINICAL LEGAL EDUCATION (CLE) IN CONTEXT OF INJURY OFFENCE LIABLE TO QISAS UNDER THE BRUNEI SYARIAH PENAL CODE ORDER 2013 - Haji Aji, Rajali; Masum, Ahmad; Abu Bakar, Yusuf Sani (Journal of Islamic, Social, Economics and Development, 2024)
Nations across the globe are actively progressing towards achieving the Sustainable Development Goals or SDGs. One of the SDGs is in education. Clinical Legal Education (CLE) is a part of learning which is pivotal in the study journey of a Law student legal education. It must co-exist with the theoretical learning method obtained from Law classrooms. Using the CLEs in legal pedagogy instils and develops professional skills in a Law student such as advocacy, client counselling, legal negotiations, legal drafting etc. Whereas on the other hand, one of the non-fatal offences against person under the Brunei Syariah Penal Code Order 2013 is the offence of causing injury or hurt liable to qisas. This is whereby for instance a person voluntarily caused another person to sustain bodily pain which is liable to the punishment of qisas or retaliation under the Order. The research employed the library-based research in order to analyze how the offence of causing injury or hurt liable to qisas under the Order is taught by legal educators and learnt by Law students using the Clinical Legal Education (CLE). The research found that the Clinical Legal Education (CLE) methods are cardinal pedagogical methods in order to produce not only theoretical but also practical-minded law graduates who will be industry ready when they enter their professional career pathway after graduation. This helps in ensuring a country’s achievement in SDGs particularly legal education.